Frequency Formats: How Primary School Stochastics Profits From Cognitive Psychology - Till, Christoph; Sproesser, Ute (Frontiers in Education, 2020)
Cognitive psychology has shown that understanding numerical information is deeply related to the format in which this information is presented; percentages are difficult to grasp whereas frequency formats are intuitively accessible. This plays a vital role in the medical domain where difficult risk-related probability judgments have to be made both by professionals and their patients. In this article, we demonstrate that the idea of representing statistical information in terms of frequency formats is not only helpful for communicating risks, but can be applied to primary school stochastics when percentages and fractions are not available. For this purpose, we report on an intervention study conducted in Grade 4 in primary school. The results show, on the one hand, that primary school students could already solve Bayesian reasoning tasks in the pretest when natural frequencies were used. On the other hand, the students profited from the intervention where they used different representations, namely colored tinker cubes and natural frequencies in order to describe and quantify frequencies and probabilities. These results go along with findings from cognitive psychology that activities with hands-on material as well as pointing out to the underlying nested-sets structure can foster Bayesian reasoning. The results are discussed in particular with regard to teaching stochastics in (primary) school.